2023
DOI: 10.1002/jcla.24886
|View full text |Cite
|
Sign up to set email alerts
|

Delayed progressive sensorineural hearing loss due to a novel compound heterozygous PTPRQ mutation in a Chinese patient

Abstract: Background:The Protein tyrosine phosphatase receptor Q (PTPRQ) gene encodes a member of the type III receptor-like protein tyrosine phosphatase family found in the stereocilium. Mutations in PTPRQ are mostly associated with deafness, autosomal recessive type 84 (DFNB 84), which usually results in progressive familial hearing loss. Methods: A 25-year-old woman and her sister, both with postlingual-delayed progressive sensorineural hearing loss, were examined. They were from a nonconsanguineous marriage and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…This variant resulted in the truncation of the protein by escaping nonsense-mediated mRNA decay and exerted a dominant-negative effect [23]. On the other hand, the loss of function variants identified in other exons were reported as causative for autosomal recessive HL (DFNB84) [7,23]. All variants identified in this study were located in exon 3 to exon 39 and no variants were located in exon 45.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…This variant resulted in the truncation of the protein by escaping nonsense-mediated mRNA decay and exerted a dominant-negative effect [23]. On the other hand, the loss of function variants identified in other exons were reported as causative for autosomal recessive HL (DFNB84) [7,23]. All variants identified in this study were located in exon 3 to exon 39 and no variants were located in exon 45.…”
Section: Discussionmentioning
confidence: 67%
“…The PTPRQ gene encodes a member of the type III receptor-like protein tyrosine phosphatase family, and PTPRQ is known as one of the causative genes for non-syndromic SNHL without inner malformation. PTPRQ-associated HL is a relatively rare genetic cause of HL, with only about 30 causative PTPRQ variants reported to cause SNHL [7]. In this study, we identified 17 variants from 13 HL patients, which is the largest number of patients yet to be detected.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations